Safety and efficacy of glibenclamide on functional outcomes in ischemic and hemorrhagic stroke: a systematic review and meta-analysis of randomized clinical trials - Shilash, Ola Bin; Alhathlol, Hussam; Alduhaysh, Rana; Almufarriji, Razan; Bafaquh, Mohammed (Frontiers in Neurology, 2025)
BackgroundSecondary brain injuries, including delayed cerebral ischemia, neuroinflammation, and stroke induced cerebral edema can occur following both ischemic and hemorrhagic strokes, contributing to a negative impact on clinical outcomes. Glibenclamide, a sulfonylurea antidiabetic medication, has shown potential in minimizing these consequences by targeting the SUR1-TRPM4 channel. However, glibenclamide’s therapeutic effectiveness and safety in stroke patients remain unknown. Therefore, this systematic review aims to assess the safety and efficacy of glibenclamide in improving outcomes following both ischemic and hemorrhagic strokes.MethodsFour databases were searched for RCTs published up to November 2024. Studies were included if they involved adult patients with ischemic stroke, hemorrhagic stroke, or subarachnoid hemorrhage, and reported relevant safety and efficacy outcomes. Efficacy outcomes were measured using the Modified Rankin Scale at 3 and 6 months. Safety outcomes included adverse events such as hypoglycemia, hydrocephalus, and mortality.ResultsData from six RCTs, involving 555 patients (280 intervention, 275 control), were included: 4 trials in subarachnoid hemorrhage, one trial in ischemic stroke, and one in hemorrhagic stroke. At 3 months, the pooled odds ratio (OR) for poor functional outcomes was 0.98 (95% CI: 0.65–1.48), and at 6 months, 0.52 (95% CI: 0.24–1.12; p = 0.094), with no significant differences between glibenclamide and placebo. Safety analysis showed a significant increase in symptomatic hypoglycemia (OR 4.69, 95% CI: 1.45–15.23; p = 0.010) but no significant differences for hydrocephalus (OR 1.60, 95% CI: 0.76–3.37; p = 0.220) or mortality (OR 0.57, 95% CI: 0.32–1.05; p = 0.071). Delayed cerebral ischemia (DCI) showed a borderline reduction in risk (OR 0.43, 95% CI: 0.18–1.00; p = 0.051) in the treatment group.ConclusionIn patients with ischemic or hemorrhagic stroke, glibenclamide demonstrates a favorable safety profile but shows limited efficacy in improving functional outcomes. The elevated risk of hypoglycemia emphasizes the necessity of using this medication with caution.